Protective In Vivo Effects Of Curcumin On Chromium Induced Genotoxicity In Germ Cells Of Mice - K. RUDRAMA DEVI,; M. MOSHE RAJU, (International Journal of Pharma and Bio Sciences, 2012)
Hexavalent chromium has been reported to be as potent carcinogen mutagen, teratogen. It is used in metallurgical, tanning leather industries etc., It is very important to reduce its toxicity.In the present study, the animals were grouped as I – IV. In group - I animals treated only normal saline, Group – II received 60 mg/kg of chromium IV once in week for five weeks, Group – III the animals were administered with 10 mg/kg/day curcumin daily, Group IV were treated with curcumin 10 mg/kg daily + chromium 60 mg/kg once in a week for 35 days.Chromium treated animals showed a significant decrease in sperm count and an increase in sperm head abnormalities. However the combined treatment of curcumin and chromium restores the sperm count and decrease the percentage of sperms with head abnormalities. This study indicates that administration of curcumin prior to chromium night prevent the germ cell damage in swiss albino male mice.